Gerakan Agraria di Tapanuli Utara Awal Orde Baru (1971–1979) - Lasron P. Sinurat (Lembaran Sejarah, 2022)
Under the New Order government, the control of agrarian resources by the state was a way to ensure development programs that increased the country's economic income. This control is legitimized by agrarian political policies, including management through Law no. 5 of 1967 concerning the Basic Provisions of Forestry. In North Tapanuli, expanding the state forest area as mandated by the Forestry Law is a new chapter in the struggle for land rights, and triggers the emergence of community resistance movements. This article will discuss the history of the agrarian movement in North Tapanuli in 1971-1979. People's resistance signifies the inaccuracy of rural communities in the development of the country.